Rapid biological synthesis of silver nanoparticles from Cymbopogon citratus extract and evaluation of its antimicrobial properties - Muntasir, Mohammed Nimeree (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.